Um olhar sobre migração, interculturalidade e educação : alunos migrantes na escola municipal de Boa Vista/RR - Silva, Maria José Barroso (2021)
In this research, we worked with the idea of cultural diversity in connection with educational processes in the Venezuelan migratory context that presents itself in the State of Roraima, significantly from 2017. For this, a reflective analysis of the theories that address contexts was necessary, that contrast identities and differences, alterity in cultural diversity and education, with an emphasis on the inclusion of migrants in the education system as a consequence of human mobility. We refer to Silva's (2000) perspective on the identity process relating to otherness, based on Hall (2002)'s concepts regarding the subject's identity concept, also Silva (2018), Sebbah (2009), Ruiz (2008 ), Ribeiro (2015) and Lévinas (1980), when they talked about identity in this encounter with alterity or the other. Thus, from this reflection, we seek to investigate the development of existing interculturality from the inclusion of migrant students in the Brazilian education system, in order to understand the public policies of the Municipal Education Department of Boa Vista RR, for the reception of students migrants, from Curriculum Documents of the Municipal Education System of Boa Vista Roraima. The field research took place at the Juslany de Souza Flores Municipal School, through the analysis of enrollment documentation from 2016 to 2020, in the school secretariat and teaching materials in coordination, direction, classrooms and teachers' planning. With this, the intention was to analyze the leveling of migrant students in municipal schools, seeking to find out about the adequacy of the teaching material given the cultural diversity involved in the participation of migrant students inserted in the municipal education teaching system. We believe that reflecting on the reception process and its implications for the dynamics of the school system, at a time of strong migratory demand, can contribute to improvements in the assistance provided to migrant students. It was found that at Juslany de Souza Flores Municipal School, the school community lives in a context of confluence of cultures, which is evidenced by the communication challenge that poses a lack of knowledge in Spanish and Portuguese. Perhaps this issue is a force to take the paths of interculturality that are needed to respond to the conditions that the educational and multicultural reality of Roraima presents today.